The Relationship between Happiness at Work and Performance in Hybrid Working Employees in the Era of Digital Transformation - Sudrajat, Ellena Kristy; Hastuti, Rahmah (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This study examines the relationship between happiness at work and performance of hybrid employees in the era of digital transformation. Hybrid work systems, which combine working from home and the office, have become increasingly popular in the post-COVID-19 pandemic as they improve work-life balance. Happiness at work, which includes engagement, job satisfaction, and affective organizational commitment, is hypothesised to be related to performance. Using a quantitative approach with a correlational design, this study involved 220 hybrid employees in Jabodetabek. The measurement tools used were Happiness at Work Scale and Individual Work Performance Questionnaire. The results of Spearman analysis showed a significant positive relationship between happiness at work and performance (r = 0.546, p < 0.001). These results confirm that happiness at work contributes to improved performance. Organisations need to support employee well-being through work flexibility and effective technology to increase productivity.